2021
DOI: 10.3389/fgene.2021.666015
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in Mammary Gland Epithelial Cells Unraveling Potential Difference in Milk Production Between Jersey and Kashmiri Cattle Using RNA Sequencing

Abstract: Deep RNA sequencing experiment was employed to detect putative single nucleotide polymorphisms (SNP) in mammary epithelial cells between two diverse cattle breeds (Jersey and Kashmiri) to understand the variations in the coding regions that reflect differences in milk production traits. The low milk-producing Kashmiri cattle are being replaced by crossbreeding practices with Jersey cattle with the aim of improving milk production. However, crossbred animals are prone to infections and various other diseases re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In ruminants, ABC is equally important. Ahmad et al found that the expression of ABC varies significantly among different milk yields by RNA-seq [103]. Since the expression of ABC is also different between different breeds of cattle, the difference in immunity may also be related to ABC.…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 99%
“…In ruminants, ABC is equally important. Ahmad et al found that the expression of ABC varies significantly among different milk yields by RNA-seq [103]. Since the expression of ABC is also different between different breeds of cattle, the difference in immunity may also be related to ABC.…”
Section: Atp-binding Cassette (Abc)mentioning
confidence: 99%
“…It has been reported that human breast milk leptin during the first stages of lactation may regulate processes that affect infant weight gain from the first to the sixth month 51 . FZD9 has been reported to be associated with lipid metabolism during lactation, quantity of milk produced 52 , pregnancy and, fertility 53 which can support the role of this gene in the weight of lambs at birth. It has been reported that the MDH2 gene is less expressed in leaner pig breeds, and also, in general, this gene is expressed at higher levels in females than in males 54 , which could be concluded that this gene is related to body weight.…”
Section: Discussionmentioning
confidence: 80%
“…In llama, most of the selection signatures encompasses loci involved in the regulation of reproduction and maternal traits: some are involved in the lipid metabolism during lactation, as ARFGEF2 and FZD9 which are known for their role in fatty acid transport [ 36 ] adipocytes differentiation [ 37 ] and quantity of milk produced [ 38 ]. Similarly, the PHF20 gene is involved in milk production [ 39 ] and lactating efficiency [ 40 ], while RCOR1 is a candidate gene implicated in lactose synthesis and milk yield [ 41 ].…”
Section: Discussionmentioning
confidence: 99%